Overview Of Village Fund Allocation By Number Of Villages - Heru Kreshna Reza; Kurniati Karim; Melly Susanti (Publisher Cv. Inara, 2022)
The existence of regional autonomy can increase regional income, villages can be more independent in managing village finances. This type of quantitative descriptive research will answer how big is the relationship between the Village Fund Allocation (ADD) given to each district and the number of villages. The populace in this review is the breakdown of town assets by area/city for monetary year 2020. Furthermore the example utilized in this review is subtleties of town assets by area/city for financial year 2020 in Bengkulu Province, which are 9 areas. The outcomes observed that the assignment of town subsidizes given to every area was as per the Regulation of the Minister of Finance of the Republic of Indonesia No. 193/Pmk.07/2018, however the aftereffects of the connection test showed that the connection between the allotment of town assets to the 9 locale and the quantity of towns shows the relationship that Average is equivalent to 0.411.